Pendidikan Profesional Untuk Wartawan - Rusdiono Mukri (Institut Agama Islam Sahid (INAIS) Bogor, 2019)
The research and writing of this paper is intended to provide input or suggestions to the management of press publishing in order to provide solutions to human resource quality problems in the field of journalism. Professional journalists hold firm journalistic ethics. Adherence to the code of conduct is one of the characteristics of professionalism, in addition to expertise, attachment and freedom. With the code of ethics guidelines, a journalist will not confuse facts and opinions in writing news; will not write slander, sadistic, and obscene news; will not